2014
DOI: 10.5539/gjhs.v7n3p161
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Depression and Malnutrition on Health-Related Quality of Life Among the Elderly Iranians

Abstract: Introduction:The present study aimed to assess the association between nutritional status and depressive symptoms among elderly Iranians and to explore their impact on their Health-Related Quality of Life (HRQoL).Methods:In this cross-sectional study, 447 elders aging from 55 to 85 years were randomly selected and completed the Iranian version of Geriatric Depression Scale-15 (GDS), Mini Nutritional Assessment (MNA), and the Iranian version of Short Form Health Survey (SF-36).Results:Out of the 447 elderly, 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 34 publications
10
31
0
4
Order By: Relevance
“…The overall poor QOL observed in this study is consistent with previous studies from Nepal's capital city of Kathmandu, where older patients in an outpatient clinic [16] and nursing homes [17] settings, had a lower overall QOL score. Previous studies, from international settings, are in line with our findings [22,23]. Further, a gradient decline in the odds of poor QOL was noted by increasing age group which is in line with a previous study from Nepal where age was inversely associated with QOL [24].…”
Section: Discussionsupporting
confidence: 93%
“…The overall poor QOL observed in this study is consistent with previous studies from Nepal's capital city of Kathmandu, where older patients in an outpatient clinic [16] and nursing homes [17] settings, had a lower overall QOL score. Previous studies, from international settings, are in line with our findings [22,23]. Further, a gradient decline in the odds of poor QOL was noted by increasing age group which is in line with a previous study from Nepal where age was inversely associated with QOL [24].…”
Section: Discussionsupporting
confidence: 93%
“…Given the results, the comparative study of the QOL among the elderly is sought. The female majority in the sample is close to other findings [26][27][28]. Even given this reality in both scenarios, the gender was not significantly associated with QOL.…”
Section: Discussionsupporting
confidence: 57%
“…Having a strong connection to this domain, the depression had an important focus when evaluating the mental and emotional aspects of the QOL of the elderly [28]. Recently, low QOL scores have been found in elderly patients with depressive symptoms when compared to elderly patients without these symptoms [26].…”
Section: Discussionmentioning
confidence: 99%
“…According to BMI, the depression is high among the elderly who were underweight and according to MNA scale, the depression is high among malnourished (88.9%) and among the elderly at risk of malnutrition (76.1%) when compared to the elderly who were having normal nutritional status and is corroborated with some studies. (21,24,25)Depression is significantly associated with the presence of anemia among the elderly and is supported by a study done in Chianti (26) and in Sao Paulo (27)As the severity of anemia increases, the proportion of depression also increases from 36.4% in the elderly with mild anemia to 61.9% in the elderly with severe anemia. Binary logistic regression analysis showed that the increase in the burden of depression is significantly associated with lower socio economic status,the elderly who were widow/widower/ separated compared to currently married, the elderly who are malnourished or at risk of malnutrition and the presence of co-morbidities.…”
Section: Discussionmentioning
confidence: 52%